2019
DOI: 10.1182/bloodadvances.2019000360
|View full text |Cite
|
Sign up to set email alerts
|

Distinct immune composition in lymph node and peripheral blood of CLL patients is reshaped during venetoclax treatment

Abstract: Morbidity and mortality due to immunosuppression remain among the foremost clinical challenges in chronic lymphocytic leukemia (CLL). Although immunosuppression is considered to originate within the lymph node (LN) microenvironment, alterations in T and natural killer (NK) cells have almost exclusively been studied in peripheral blood (PB). Whereas chemoimmunotherapy further deteriorates immune function, novel targeted agents like the B-cell lymphoma 2 inhibitor venetoclax potentially spare nonmalignant lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
82
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 64 publications
11
82
2
2
Order By: Relevance
“…Importantly, the activation of all immune cells in the majority of our patients receiving novel drugs was more pronounced compared with those previously treated with immunochemotherapy or untreated patients, even after correction for CLL cell number. In line with our data, a recent study using venetoclax-based regimens revealed a reduction in the immunosuppressive footprint of CLL, suggesting that immune system regeneration occurs after removal of leukemic cells [45]. Similarly, ibrutinib has been shown to modulate the immunosuppressive CLL microenvironment, through STAT3-mediated suppression of regulatory B-cell function and inhibition of the PD-1/PD-L1 pathway [46].…”
Section: Hla-dr Expression On Monocyte Subpopulations Does Not Differsupporting
confidence: 89%
See 2 more Smart Citations
“…Importantly, the activation of all immune cells in the majority of our patients receiving novel drugs was more pronounced compared with those previously treated with immunochemotherapy or untreated patients, even after correction for CLL cell number. In line with our data, a recent study using venetoclax-based regimens revealed a reduction in the immunosuppressive footprint of CLL, suggesting that immune system regeneration occurs after removal of leukemic cells [45]. Similarly, ibrutinib has been shown to modulate the immunosuppressive CLL microenvironment, through STAT3-mediated suppression of regulatory B-cell function and inhibition of the PD-1/PD-L1 pathway [46].…”
Section: Hla-dr Expression On Monocyte Subpopulations Does Not Differsupporting
confidence: 89%
“…The crucial impact of CLL bulk on blood microenvironment observed in our study is also supported by a recent study showing that CLL cells impair mitochondrial fitness in CD8+ T cells and impede CAR T-cell efficacy [29]. Also other studies showed that CLL cells are active participants in microenvironmental cross-talk [30] contributing to the inhibition of effective immune cell activation by production of spectrum of immunosuppressive mediators [12,31,32], most prominently in the lymph nodes [31]. Here we provide evidence of the immunosuppressive condition also in circulation in CLL.…”
Section: Hla-dr Expression On Monocyte Subpopulations Does Not Differsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, we noted a population of EOMES + PD-1 + CD4 + T-cells in LN samples of CLL as well as DLBCL patients. In the follicles of secondary lymphoid organs, tight interactions of T- and malignant B-cells take place, which lead to activation and, in case of persistent exposure to antigens, to T-cell exhaustion (37, 47) which might contribute to the observed phenotype of T-cells in CLL and DLBCL LNs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therapeutic agents for CLL have immunomodulatory effects that can potentially alter the risk of contracting and the response to infection. 3,4 The interface of SARS-CoV-2 infection, severity of COVID-19 symptoms, and active treatment of CLL represents a major therapeutic dilemma-should CLL-directed therapy continue or be held? This is particularly true for patients receiving B-cell receptor kinase inhibitors, where abrupt treatment discontinuation can result in rapid decompensation in some patients that could mimic COVID-I9 symptoms.…”
mentioning
confidence: 99%